Norfloxacin disposition after sequentially increasing oral doses. - Swanson, B N (1983)
Single doses of norfloxacin (200, 400, 800, 1,200, and 1,600 mg) or placebo were administered orally at weekly intervals to 14 healthy male volunteers in a double-blind study. Norfloxacin was measured in serum and urine by high-pressure liquid chromatography with UV detection. The concentrations of this drug in serum peaked 1 to 2 h after each dose; the mean peak values for increasing doses were 0.75, 1.58, 2.41, 3.15, and 3.87 micrograms/ml. Mean area under the serum concentration-time curves for the first 12 h after each dose were 3.56, 6.26, 11.4, 16.1, and 19.7 micrograms . h/ml, respectively. The elimination half-life of norfloxacin was about 7 h and was similar for all doses. The concentrations of the drug in urine also peaked 1 to 2 h after dosage; mean peak values for increasing doses were 200, 478, 697, 992, and 1,045 micrograms/ml. Renal clearances approximated 285 ml/min. About 30% of each dose was excreted into urine as unmetabolized norfloxacin. Crystals of the drug were occasionally observed during microscopic examination of freshly voided urine collected after the 1,200- and 1,600-mg doses. Crystalluria was not encountered at lower doses.